Lenalidomide-dexamethasone versus observation in high-risk smoldering myeloma after 12 years of median follow-up time: A randomized, open-label study. (October 2022) - Mateos, María-Victoria; Hernández, Miguel-Teodoro; Salvador, Carlos; Rubia, Javier de la; de Arriba, Felipe; López-Corral, Lucía; Rosiñol, Laura; Paiva, Bruno; Palomera, Luis; Bargay, Joan; Oriol, Albert; Prosper, Felipe; et al.
Abstract: Background: Smoldering multiple myeloma (SMM) is a heterogeneous disease in terms of progression to myeloma (MM), but its standard of care continues to be observation. Methods: The QuiRedex phase 3 trial initiated in 2007 included 119 high-risk patients with SMM randomized to treatment or observation. Treatment consisted of nine 4-week induction cycles (lenalidomide [Rd], 25 mg on days 1–21 plus dexamethasone, 20 mg on days 1–4 and 12–15), followed by maintenance (R, 10 mg on days 1–21) for up to 2 years. The primary end-point was time to progression (TTP) to myeloma based on per protocol population. Secondary end-points were overall survival (OS), response rate, and safety. An update of the trial after a long-term follow-up is presented here. This trial was registered with ClinicalTrials.gov (NCT00480363). Findings: After a median follow-up time of 12.5 years (range: 10.4–13.6), the median TTP to MM was 2.1 years in the observation arm and 9.5 years in the Rd arm (HR: 0.28, 95% CI: 0.18–0.44, p < 0.0001). The median OS was 8.5 years in the abstention arm and not reached in the Rd group (HR: 0.57, 95% CI: 0.34–0.95, p = 0.032). Patients who progressed received optimized treatments according to the standards of care, and the OS from progression was comparable in both arms (p = 0.96). Interpretation: This analysis confirms that early treatment with Rd for high-risk SMM translates into a sustained benefit in both TTP and OS. Funding: Pethema (Spanish Program for the Treatment of Hematologic Diseases), Spain. Highlights: High-risk smoldering presents a 50% progression risk to active myeloma at 2 years. Early treatment has demonstrated to delay the progression to myeloma. Rd confirms the sustained benefit in TTP and OS in high-risk smoldering. Many trials are ongoing to support the role of early detection and intervention.